2003
DOI: 10.1614/wt02-151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Common Wheat (Triticum aestivum) Management Alternatives on Weed Seed Production1

Abstract: Common management alternatives were compared in a factorial arrangement for 2 yr to determine their effects on green foxtail and yellow foxtail seed production in spring wheat in the Northern Great Plains of the United States. Seed production was measured twice, at wheat harvest (in August) and postharvest (after first lethal frost in autumn). Management alternatives were early, middle, and late crop-sowing dates; no-till, chisel, and moldboard plow tillage systems; and broadleaf herbicide only and broadleaf h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
7
0
4
Order By: Relevance
“…In 1996, yellow foxtail panicles were slightly larger than similar plants in 1997 (Table 4), but this fact does not give insight into the disparity in seed production. Kegode et al (2003) reported that late sowing can reduce the size of foxtail panicles, but this was not consistent for yellow foxtail over a 2-yr period. Yellow foxtail plants that emerged late had longer panicles in 1996 (16%) than in 1997, when they were 28% shorter.…”
Section: Seed Productionmentioning
confidence: 94%
See 2 more Smart Citations
“…In 1996, yellow foxtail panicles were slightly larger than similar plants in 1997 (Table 4), but this fact does not give insight into the disparity in seed production. Kegode et al (2003) reported that late sowing can reduce the size of foxtail panicles, but this was not consistent for yellow foxtail over a 2-yr period. Yellow foxtail plants that emerged late had longer panicles in 1996 (16%) than in 1997, when they were 28% shorter.…”
Section: Seed Productionmentioning
confidence: 94%
“…Green foxtail, on the other hand, responded uniformly between 1996 and 1997 with a 10 to 34% reduction in panicle length when crop sowing was delayed (Kegode et al 2003). In our study, the absence of significant interactions with tillage system, the consistently higher number of primary tillers and panicles per plant in NT and MP compared with other tillage systems (Table 2), and consistently higher seed production in NT corn compared with other tillage systems ( Figure 3) show that relatively reliable estimates for seed production were obtained for this species.…”
Section: Seed Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was reflected in the low amount of nitrogen in their seed and biomass, which suggests that the presence of flax and red clover caused a reduced availability of nutrients for the weeds (Norris et al 2001;Weiner et al 2001). This suggests that flax intercropping with red clover or growing alone, limited the access to resources for the weed, thus affecting their offspring, as noted by Martinez-Ghersa et al (2000) and Kegode et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is also expected that these practices can reduce the availability of resources for weeds and adversely affect their growth by diminishing their reproductive capacity (Kegode et al 2003), thus, acting as a suppressor, a suitable feature for long-term weed management.…”
Section: Introductionmentioning
confidence: 99%